Factors Affecting the Learning of Fixed Prosthodontics Course by Students at Kermanshah University of Medical Sciences - Moradpoor, Hedaiat (Open Access Maced J Med Sci, 2019)
AIM: The objective of this study was to investigate the factors affecting the learning of fixed prosthodontics course from the viewpoint of students and faculty members of Kermanshah Dentistry School. MATERIAL AND METHODS: This research was a descriptive-analytical study conducted using the convenient sampling method. A total of 72 students and 5 faculty members were included in the study. Data were collected using a researcher-made questionnaire containing two sections. The first section consists of demographic information, and the second section consists of 14 questions to evaluate the factors affecting the learning of the fixed prosthodontics course. RESULTS: From the students’ point of view, there was a significant relationship between the effect of using clinical points during a teaching on the learning efficacy of the fixed prosthodontics course and gender (P = 0.028). There was a statistically significant relationship between the level of professor’s knowledge regarding the modern educational methods on the learning of fixed prosthodontics course (P = 0.034). The factor of displaying and implementing practical work on the real patient was considered important by students, and having knowledge about modern educational methods was considered important by faculty members. CONCLUSIONS: It is recommended that appropriate educational planning be implemented to enhance students’ practical work on the real patient and increase professors’ knowledge about modern educational methods.